Objects of Oppression: An Ecofeminist Reading of Tar Baby by Toni Morrison - Güngör, Pınar Süt (My University, 2023)
Formulated in the twentieth century, ecofeminism is a body of literature that seeks to identify the relationship between the oppression of nature and women. In this context, the traditional roles of nature and women have been examined in various social fields, such as literature, philosophy, sociology, and psychology. Although its historical roots go back to the 1970s, this approach gained wider recognition in the 1990s, with current developments in different fields. As the theoretical background of this study, ecofeminism clarifies the conceptual links, especially in patriarchal societies, between nature and women, in terms of domination, oppression, colonialism, sexism, and racism. This study attempts to analyze Toni Morrison’s novel Tar Baby (1981) by applying principles and considerations of ecofeminism through male/female and human/non-human dichotomies. As a writer who is concerned with all varieties of domination, Morrison, in Tar Baby, foregrounds the exploitation of nature to raise ecological awareness and wisdom, and to mark the fragmentation, displacement, and assimilation of women in a male-dominated world. This study confirms that there is a strong link between the oppression of nature and the oppression of women in male-dominated societies.